PENGARUH PENGALAMAN KERJA DAN FASILITAS KERJA TERHADAP KINERJA KARYAWAN MELALUI MOTIVASI KERJA SEBAGAI VARIABEL INTERVENING PADA KSP PEKALI 99 KABUPATEN SITUBONDO - Mustaqimah, Siti; Karnadi, Karnadi; Pramesthi, Riska Ayu (Fakultas Ekonomi dan Bisnis, 2022)
The purpose of the study was to determine the effect of work experience and work facilities on employee performance through work motivation as an Intervening Variable at KSP Pekali 99 Situbondo Regency. The sample in this study were 50 employees of KSP Pekali 99 Situbondo Regency. The sampling technique was determined with a saturated sample. Data analysis and hypothesis testing in this study used the Structural Equation Model – Partial Least Square (PLS-SEM) The results of the direct influence hypothesis test using the Smart PLS 3.0 application, show that work experience has a positive but not significant effect on work motivation, work facilities have a positive and significant effect on work motivation, work experience has a positive and significant effect on employee performance, work facilities have a positive and significant effect on employee performance, work motivation has a positive and significant effect on employee performance. The results of the indirect hypothesis test show that work experience has no positive but not significant effect on employee performance through work motivation, work facilities have a positive and significant effect on employee performance through work motivation